Perlukah Strategi Marketing dalam Pemilihan Kepala Desa (Pekon)? - Arum Arupi Kusnindar (Valid: Jurnal Ilmiah, 2021)
Marketing in politics is an interdisciplinary concept, namely politics, communication and marketing and involves the process of analysis, development and implementation of marketing strategies to direct opinions in choosing constituents. Marketing in the political field is strongly influenced by special conditions in an area, therefore, marketing strategies that are successful in one area are not always successful in other areas. This research is a quantitative research with a questionnaire as a data collection instrument. The study was conducted in five villages in Pringsewu Regency. The results showed that there was no difference in marketing strategy among village heads. However, there are differences in the preferred approach. This research is expected to encourage further research on marketing in the political field, especially in the era of information technology with a technological approach